COVID-19 cluster investigation after choir recording at Church X Bantul Regency in 2021 - Nur Hayati; Puspitarani, Fitriana; Nugroho, Andri Setyo Dwi; Indriani, Citra (BKM Public Health and Community Medicine, 2021)
Objective: On 29 May 2021 PHC Imogiri 1 obtains information about a positive COVID-19 patient in their area. The confirmed case was attending a choir at Church X on 19 May 2021. An epidemiological investigation was carried out to confirm the existence of the COVID-19 cluster, describe the attack rate, and provide recommendations for future cluster control. Method: This study is a descriptive epidemiological study. The case definition is people involved in the church X recording process and their close contact with the results of laboratory tests using RT-PCR positive for COVID-19 in Bantul from May-June 2021. Data were obtained via E-form using a standardized questionnaire and direct observation at the church. Results: 28 participants consisting of 21 singers, 1 conductor, 6 multimedia teams involved in a choir. The indoor rehearsal was in a closed space with closed windows. There were a total of 57 including contacts and choir members with 42.1% tested positive. One case was hospitalized (4.2%), and three cases were isolated in shelters (12.5%). Most of the cases were asymptomatic (70.8%), and the most common symptoms were fever (12.5%) and cough (12.5%). The majority of cases were female (71%), belong to age group 25-34 years (25%), followed with 35-44 years (20.8%), and 55-64 years (20.8%). Attack rate based on the vocal range of Alto 2 (AR=100%) and soprano 1 (AR=83%). interviews with church councils during the recording process singers only used a faceshield as PPE. Conclusion: A cluster transmission occurred in Church X after a choir recording. The use of the mask is necessary during choir or indoor activity especially in a closed space with poor ventilation. It is also necessary for stakeholders to strengthen and emphasize the importance of health protocols, including using masks and avoiding gathering in large groups to control the spread of COVID-19 in a closed space.